Exploring the Effect of Jiawei Buguzhi Pills on TGF-β-Smad Pathway in Postmenopausal Osteoporosis Based on Integrated Pharmacological Strategy. (31st October 2021) - Yuan, Xiao; Wu, Yonghe; Yang, Kailin; Liu, Huiping; Zhang, Guomin
Abstract : Objective . To explore the effect of Jiawei Buguzhi Pills (JWBGZP) on the TGF- β -Smad pathway in postmenopausal osteoporosis (PMO) based on integrated pharmacological strategy. Method . The ETCM database was used to collect JWBGZP. GeneCards and OMIM databases were utilized to obtain PMO-related genes. Cytoscape was used for network construction and analysis, and DAVID was used for GO and KEGG enrichment analysis of key targets. Animal experiments and cell experiments were conducted to further explore the mechanism. The bone mass density was detected by dual-energy X-ray bone densitometer. The TGF- β 1 and Smad4 mRNA in bone tissue were detected by RT-qPCR. The TGF- β 1 and Smad4 protein in bone tissue were detected by the western blot. The TGF- β 1 and Smad4 protein in osteoblasts were determined by immunohistochemistry. Result . A total of 721 JWBGZP potential targets and 385 PMO-related genes were obtained. The enrichment analysis showed that JWBGZP may regulate the TGF-beta signaling pathway, oxidation-reduction process, aging, response to hypoxia, response to ethanol, negative regulation of cell proliferation, PI3K-Akt, HIF-1, and other signaling pathways. The animal experiments showed that compared with the model group, the femoral bone mineral density and lumbar bone mineral density of the JWBGZP group increased ( P  < 0.05); the expression levels of TGF- β 1 and Smad mRNA and proteins in the JWBGZP group were significantly higher ( P  < 0.05). The cell experiment results showed a large number of osteoblast stained blue-purple and orange-red calcified nodules. The expression levels of TGF- β 1 and Smad proteins in the JWBGZP group were significantly higher than those in the blank control group and the sham operation group, and the protein expression levels in the model group were the lowest ( P  < 0.05). Conclusion . JWBGZP may be involved in PI3K-Akt, HIF-1, estrogen, prolactin, and other signaling pathways and regulate MAPK1, AKT1, PIK3CA, JAK2, and other gene targets, regulate bone metabolism, and thereby treat PMO.